Enhancing Pre-Service Teachers' Resilience to Overcome Chemistry Anxiety: Self-Determination Theory Approach - Boateng, Sakyiwaa; Mudadigwa, Brighton (IJCER (International Journal of Chemistry Education Research), 2025)
This study investigates the influence of Self-Determination Theory (SDT) as a construct to help pre-service teachers mitigate chemistry anxiety as they build resilience in the subject. The study was framed within the three key sub-constructs of autonomy, competence, and relatedness under SDT as a theoretical lens.  The study employed sequential mixed methods research approaches and sampled pre-service teachers from two South African universities, one university being in the urban area and the second university in the rural area. Whole-class interventions were employed in each institution where the researchers incorporated a resilience toolkit over a semester. Questionnaires and interviews were the main instruments used to collect data. The data was analysed using descriptive statistics and thematic analysis. The study found that pre-service teachers generally experienced anxiety in chemistry, and that female pre-service teachers displayed statistically significant anxiety scores compared to males (p = 0.018); whereas the location of the university had no statistically significant influence on anxiety scores (p = 0.896). The study further found that the interventions improved emotional regulation, competence, and intrinsic motivation while fostering supportive peer networks.  The study recommends integrating resilience-building strategies into science teacher training programs to equip pre-service teachers with skills to manage science anxiety effectively.